Trend Berhijab Di Kalangan Remaja dan Pengaruhnya Terhadap Sikap dan Perilaku Dalam Pergaulan di MA Keterampilan NW Pancor - Elfa Yuliana; Ummy Khusnul Yaqien (STAI AL-AMIN, 2026)
This study aims to determine the trend of wearing hijab among teenagers and its influence on attitudes and behavior in daily social interactions, as well as to identify the factors that encourage female students at MA Keterampilan NW Pancor to wear hijab. The method used in this study is qualitative research through a phenomenological approach, which is a study that seeks to find the essence of meaning from a phenomenon experienced by several individuals. To apply phenomenological research, the researcher chose transcendental phenomenology, in which the researcher attempts to study a phenomenon by setting aside preconceptions about it. The analysis is based on horizontalization, in which the researcher attempts to study the data by highlighting important statements from participants to provide a basic understanding of the phenomenon. The results of the study show that the trend of wearing the hijab among teenagers, especially at MA Keterampilan NW Pancor, and its influence on attitudes and behavior is more positive and it can be concluded that the driving factors influencing female students to wear the hijab are family, personal, and school environment factors. Those who wear the hijab are more polite in their speech and behavior, better at maintaining their composure when interacting with the opposite sex, and more in control of their attitudes and actions, refraining from acts that violate Islamic law. These changes can be seen in terms of their relationship with Allah, themselves, and other fellow human beings.